2015
DOI: 10.1038/cdd.2015.13
|View full text |Cite
|
Sign up to set email alerts
|

The Fcp1-Wee1-Cdk1 axis affects spindle assembly checkpoint robustness and sensitivity to antimicrotubule cancer drugs

Abstract: To grant faithful chromosome segregation, the spindle assembly checkpoint (SAC) delays mitosis exit until mitotic spindle assembly. An exceedingly prolonged mitosis, however, promotes cell death and by this means antimicrotubule cancer drugs (AMCDs), that impair spindle assembly, are believed to kill cancer cells. Despite malformed spindles, cancer cells can, however, slip through SAC, exit mitosis prematurely and resist killing. We show here that the Fcp1 phosphatase and Wee1, the cyclin B-dependent kinase (c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 20 publications
(65 reference statements)
2
47
0
Order By: Relevance
“…The two so far described APC/C Cdc20 inhibitors, TAME and Apcin, appear promising molecules as they efficiently block mitosis exit in preclinical studies, but are not yet available for clinical use (Zeng et al 2010, Sackton et al 2014. To prevent mitotic slippage, we have proposed a different strategy: inhibiting WEE1, a crucial kinase in the slippage mechanism (Visconti et al 2015a), in combination with AMCDs. Given the clinical availability of a WEE1 inhibitor, it would be worth establishing clinical trials in which the WEE1 inhibitor is combined with AMCDbased therapy.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The two so far described APC/C Cdc20 inhibitors, TAME and Apcin, appear promising molecules as they efficiently block mitosis exit in preclinical studies, but are not yet available for clinical use (Zeng et al 2010, Sackton et al 2014. To prevent mitotic slippage, we have proposed a different strategy: inhibiting WEE1, a crucial kinase in the slippage mechanism (Visconti et al 2015a), in combination with AMCDs. Given the clinical availability of a WEE1 inhibitor, it would be worth establishing clinical trials in which the WEE1 inhibitor is combined with AMCDbased therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we have demonstrated that targeting FCP1 or WEE1 by siRNAs delayed SAC adaptation and mitotic slippage in taxane-treated cancer cell lines. Moreover, remarkably, we have shown that, in vinca alkaloid-treated primary leukemic blasts isolated from bone marrow specimens of lymphoblastic leukemia patients, the addition of AZD1775 significantly prolonged mitosis, resulting in reduced viability (Visconti et al 2015a). Thus, AZD1775, by delaying mitotic slippage, limits the occurrence of AMCD resistance in cell cultures, a promising starting point to further tests in preclinical and clinical settings.…”
Section: :9mentioning
confidence: 99%
See 3 more Smart Citations